The Effects of Country of Origin and Social Media Opinion Leaders on Purchase Intention for Wuling Vehicles - Ekyawan, Fandis; Rahman, Ma’ruf Fauzi (UI Scholars Hub, 2022)
Manuscript type: Research Article Research Aims: This research objective was to analyse the influence of country of origin, trust, price perception, perceived quality and social media opinion leader on Wuling purchase intention. Design/methodology/approach: This study was conducted quantitatively by distributing questionnaires to 234 respondents who are over 20 years old and know about Wuling and selected YouTube channels. Data was analysed using Structural Equation Modelling (SEM) method with the LISREL software application. Research Findings: The results of this study indicate that there is a positive significant impact relationship between country of origin (country-related products) and trust in the purchase intention of Wuling vehicles as well as the relationship of the negative significant impact of country of origin (country-related effect) on trust and social media opinion leaders on purchase intention of Wuling vehicles. Theoretical Contribution/Originality: The findings of this study can explain the importance of country of origin cues and social media opinion leader effect on customer behaviour in their decision-making. Practitioner/Policy Implication: The managerial implication of the research is that Wuling has to reduce brand associations with China to compete in Indonesia, and Wuling has to improve the product quality, after-sales service, ease of getting spare parts and continuous innovation to get an impact and positive response. Research limitation/Implications: This study has limitations; first, the research data only relies on one platform (YouTube) in Indonesia to test hypotheses. Second, the survey was about vehicles.